2017
DOI: 10.1002/lary.26403
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite cement cranioplasty following translabyrinthine approach: Long‐term study of 369 cases

Abstract: 4. Laryngoscope, 127:2120-2125, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 33 publications
(56 reference statements)
0
31
0
Order By: Relevance
“…Our complication rates fall within these wide ranges. In the last decade, several large reports have been published with very low rates of CSF leak and wound infection, both with abdominal fat grafting and combined abdominal fat‐HAC cranioplasty . These findings are encouraging because low infection rates with the combined approach further suggest that HAC does not intrinsically lead to wound infection.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Our complication rates fall within these wide ranges. In the last decade, several large reports have been published with very low rates of CSF leak and wound infection, both with abdominal fat grafting and combined abdominal fat‐HAC cranioplasty . These findings are encouraging because low infection rates with the combined approach further suggest that HAC does not intrinsically lead to wound infection.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, cost is an important issue in the discussion of biomaterials. Prior studies have demonstrated comparable costs between HAC and other reconstructions in retrosigmoid cranioplasty, although greater HAC volume is needed for repair of translabyrinthine defects . Our institution forbids publication of contract pricing, but the national average price of a comparable formulation has been reported as $820 for 3 cc, which would yield a total price per patient of $4,000 to $7,000.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydroxyapatite has been used since the early 1990s for cranioplasty and skull base reconstruction including following translabyrinthine surgery. 7 Its superiority over bone wax in sealing bony defects and cell tracts in the petrous apex has resulted in a marked reduction in CSF leaks associated with the retrosigmoid approach. 8 …”
Section: Introductionmentioning
confidence: 99%